Regulatory effect and mechanism of LncRNA SOX2OT in idiopathic pulmonary fibrosis: Effect of LncRNA SOX2OT on lung fibers - Qiao, Man; Li, Dongsheng; He, Yuan; Cui, Qingming; Li, Xiaoqiu; Chi, Hang (Cellular and Molecular Biology, 2023)
This study discusses the role played by long noncoding RNA (lncRNA) SOX2OT (SOX2OT) in idiopathic pulmonary fibrosis (IPF). By inducing human embryonic lung fibroblasts (MRC5) through hypoxia, the researchers observed changes in SOX2OT expression and fibrotic processes during hypoxia. Moreover, SOX2OT abnormal expression vectors were constructed and transfected into MRC5 to analyze the effect of SOX2OT on MRC5. The results showed that the expression levels of SOX2OT and α-SMA were elevated under hypoxic conditions and were positively correlated (P<0.05). α-SMA, Collagen I and Collagen III protein expression and SOX2OT levels all increased under hypoxia (P<0.05). Finally, silencing SOX2OT expression led to weakened MRC5 proliferation, inhibited fibrosis process, and reduced inflammation (P<0.05). In conclusion, SOX2OT is closely related to the occurrence and development of IPF, and silencing its expression can inhibit fibrosis progression.